2000
DOI: 10.1017/s0263593300008324
|View full text |Cite
|
Sign up to set email alerts
|

Scottish Silurian shorelines

Abstract: The Silurian inliers of the Midland Valley of Scotland all exhibit a regressive sequence, and despite evident facies differences between inliers, marine successions invariably pass upwards into redbeds of continental origin. Contrasting types of shoreline facies can be seen in different inliers; here the beds in the North Esk Inlier (NEI) are compared with those previously described from Knockgardner. At Knockgardner a high energy coastal environment prevailed, but in the NEI very different conditions can be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Influxes of more sandy material provided the substrate on which the coral faunas, that gave rise to the Deerhope Coral Beds and which characterise the formation, could thrive. Clarkson et al (2001) interpreted the overlying Cock Rig Formation as the deposits of an offshore barrier system, with the flaggy mudstones and siltstones of the Deerhope Formation deposited from suspension flows below wave base on its seaward side. On the landward side of the Cock Rig offshore bar, Clarkson et al (2001) suggested that the Wether Law Linn Formation was deposited in a broad marine lagoon, perhaps several kilometres across, in which fluctuating salinities with the occasional restoration of fully marine conditions culminated in brackish or freshwater conditions.…”
Section: Silurian Succession In the Pentland Hillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Influxes of more sandy material provided the substrate on which the coral faunas, that gave rise to the Deerhope Coral Beds and which characterise the formation, could thrive. Clarkson et al (2001) interpreted the overlying Cock Rig Formation as the deposits of an offshore barrier system, with the flaggy mudstones and siltstones of the Deerhope Formation deposited from suspension flows below wave base on its seaward side. On the landward side of the Cock Rig offshore bar, Clarkson et al (2001) suggested that the Wether Law Linn Formation was deposited in a broad marine lagoon, perhaps several kilometres across, in which fluctuating salinities with the occasional restoration of fully marine conditions culminated in brackish or freshwater conditions.…”
Section: Silurian Succession In the Pentland Hillsmentioning
confidence: 99%
“…Clarkson et al (2001) interpreted the overlying Cock Rig Formation as the deposits of an offshore barrier system, with the flaggy mudstones and siltstones of the Deerhope Formation deposited from suspension flows below wave base on its seaward side. On the landward side of the Cock Rig offshore bar, Clarkson et al (2001) suggested that the Wether Law Linn Formation was deposited in a broad marine lagoon, perhaps several kilometres across, in which fluctuating salinities with the occasional restoration of fully marine conditions culminated in brackish or freshwater conditions. The red sandstones of the Henshaw Formation record the onset of predominantly terrestrial sedimentation in the Wenlock, with some evidence for minor marine incursions.…”
Section: Silurian Succession In the Pentland Hillsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above fits well with an inshore physically and chemically restricted setting, possibly a sediment-starved lagoon or analogue (cf. Clarkson et al 2001). The abundant P. dubius rhabdosomes would then indicate that pelagic graptolites occurred across the entire width of carbonate platforms and that their rarity in limestone is a result of taphonomy.…”
Section: Restricted Intra-platform Basinmentioning
confidence: 99%
“…Three-dimensionally preserved material of Bunodes from the 'Eurypterus dolomite' of Saaremaa, Estonia retains some original cuticular material and show a less pronounced sculpture (personal observations). Clarkson et al (2001) demonstrated through careful sampling, collecting and excavation that the Silurian sedimentary succession overlying the Reservoir Formation indicated a predominantly shoreline/shoreface environment, including a suite of lagoonal sediments recognised within the Wether Law Linn Formation. The exact function of this roughening of the otherwise smooth dorsal cuticular surface remains unknown.…”
Section: Relationship Of Bembicosoma With Other Synziphosurinesmentioning
confidence: 99%